Using a spreadsheet to support e-assessment - Azevedo, Jose Manuel (2018)
Some of the courses of the scientific area of Mathematics at ISCAP use multiple choice questions (MCQ) tests as a fundamental part of the assessment. The assessed topics include Differential and Integral Calculus, Algebra, Statistics, and Financial Mathematics. In the undergraduate programs of Accounting, Marketing and International Commerce, these courses are taught in theoretical-practical classes and their main objective is to provide the necessary support tools to other courses of these programs. On the other hand, these undergraduate programs, in particular Accounting, have many classes and many students, so MCQ tests have been an indispensable tool for both continuous and final exam assessment. The open source MOODLE platform, used through a local network intended only for continuous assessment, has been the support software for MCQ tests. In order to integrate student classifications so as to be more easily retrieved by all teachers, and in order to obtain them more quickly, an MS ExcelTM spreadsheet was developed. This allows us to automate the whole process from collecting the students’ answers, to obtaining their final classification and calculating important statistics. This paper describes the development process of this tool, which has proved extremely important in the e-assessment method already implemented. Therefore, some of the results presented show: (i) the substantial reduction in the time elapsed between the moment the tests were carried out by the students and the moment of the publication of the grades; (ii) the existence of automatic control in case of duplication of tests by the same student, (iii) the action of complementing MOODLE in the treatment of negative grades of students; (iv) the possibility of performing several statistical analysis that can be organized by class, by subject, by attendance regime to classes (nocturnal versus diurnal), and include comparisons with previous years and tables of frequencies of grades.